Attitudes towards disabled persons scale in Nepali: development and validation - Shrestha, Susmita; Amatya, Yogendra; Ghimire, Anup (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Continuous advocacy regarding the attitudes of individuals towards individuals with disabilities in the United States, public awareness is still mostly negative. For Persons with disabilities, research has highlighted the fact that these negative attitudes do interfere with their work environment, affecting their self-esteem and health care. Attitude of general population towards person with disability has not been studied. There is hardly any literature regarding the attitude of common people towards person with disability in Nepal. The objective was to translate and validate attitudes towards disabled persons (ATDP) scale into Nepali language. In addition, it was also attempted to compare the attitudes towards persons with disability across gender. Methods: A survey method using questionnaire was conducted and administered on people of Nepal. Attitudes toward disabled persons scale were first translated into Nepali language as per the guidelines by WHO. The translated scale was administered on 114 native Nepali speakers for validation. Internal consistency and gender differences in ATDP scores were calculated. Results: The results of the study showed that the questionnaire had good internal consistency. There was no significant difference in scores across gender. ATDP scores obtained from Nepali population were lower than the scores from other developed countries. Conclusions: The present study indicates that the translated and validated version of ATDP scale in Nepali language can be used as a standard tool in assessing attitudes towards person with disability in Nepal.